2009
DOI: 10.1007/s10681-009-9909-4
|View full text |Cite
|
Sign up to set email alerts
|

Individual reaction of Capsicum F2 hybrid genotypes in anther cultures

Abstract: The present study evaluated the individual plants reaction of F 2 hybrid generation of C. annuum: ATZ1 9 PO and ATZ1 9 CDT as well as two interspecific hybrids: C. frutescens 9 C. annuum ATM1 and C. frutescens 9 C. chinense on androgenesis conditions in in vitro anther cultures. The experiment was carried out following a modified method of Dumas de Vaulx et al. (Agronomie 1:859-864, 1981). There were demonstrated clear differences in the effectiveness of androgenesis both between the pepper hybrid forms as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
5
13
0
Order By: Relevance
“…However, selected combinations of the length of induction period on CP medium and kinetin concentration in R1 medium resulted in a successful development of androgenic embryos in the case of 15 out of the 17 morphologically different Capsicum genotypes. The strong effect of the genotype on androgenic response, reported previously (Dolcet-Sanjuan et al, 1997;Nowaczyk et al, 2009b) and also observed in this study, suggests a need to adapt anther culture conditions to particular species, cultivars, or even breeding lines. As for the C. chinense and C. baccatum species, since an effective method of androgenic embryos induction has not been developed yet, it seems reasonable to search for other modifying factors that could stimulate in vitro anther responsiveness.…”
Section: Discussionsupporting
confidence: 84%
“…However, selected combinations of the length of induction period on CP medium and kinetin concentration in R1 medium resulted in a successful development of androgenic embryos in the case of 15 out of the 17 morphologically different Capsicum genotypes. The strong effect of the genotype on androgenic response, reported previously (Dolcet-Sanjuan et al, 1997;Nowaczyk et al, 2009b) and also observed in this study, suggests a need to adapt anther culture conditions to particular species, cultivars, or even breeding lines. As for the C. chinense and C. baccatum species, since an effective method of androgenic embryos induction has not been developed yet, it seems reasonable to search for other modifying factors that could stimulate in vitro anther responsiveness.…”
Section: Discussionsupporting
confidence: 84%
“…These results agree with those obtained by Nowaczyk et al (2009) who examined the reaction of F 2 C. annuum genotypes and observed the effect of genotypes in the response to embryo induction, and variations ranged from 0 to 39 embryos in 100 anthers. Similar results were previously described by Rodeva et al (2004) and Nowaczyk and Kisiala (2006).…”
Section: Induction Of Embryogenic Calli and Embryossupporting
confidence: 91%
“…Among them, the effect of genotype on haploid embryogenesis in pepper has been shown to be the most important factor in many studies (Kristiansen and Andersen, 1993;Qin and Rotino, 1993;Mitykó et al, 1995;Rodeva et al, 2004;Gémes Juhász et al, 2009;Nowaczyk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%